New and Old Anti-CD20 Monoclonal Antibodies for Nephrotic Syndrome. Where We Are? - Basu, Biswanath; Angeletti, Andrea; Islam, Bilkish; Ghiggeri, Gian Marco (Frontiers in Immunology, 2022)
Nephrotic proteinuria is the hallmark of several glomerulonephritis determined by different pathogenetic mechanisms, including autoimmune, degenerative and inflammatory. Some conditions such as MCN and FSGS are of uncertain pathogenesis. Chimeric anti-CD20 monoclonal antibodies have been used with success in a part of proteinuric conditions while some are resistant. New human and humanized monoclonal anti-CD 20 antibodies offer some advantages based on stronger effects on CD20 cell subtypes and have been already administered in hematology and oncology areas as substitutes of chimeric molecules. Here, we revised the literature on the use of human and humanized anti-CD 20 monoclonal antibodies in different proteinuric conditions, resulting effective in those conditions resistant to rituximab. Literature on the use of human anti-CD 20 monoclonal antibodies in different proteinuric diseases is mainly limited to ofatumumab, with several protocols and doses. Studies already performed with ofatumumab given in standard doses of 1,500 mg 1.73m2 suggest no superiority compared to rituximab in children and young adults with steroid dependent nephrotic syndrome. Ofatumumab given in very high doses (300 mg/1.73m2 followed by five infusion 2,000 mg/1.73 m2) seems more effective in patients who are not responsive to common therapies. The question of dose remains unresolved and the literature is not concordant on positive effects of high dose ofatumumab in patients with FSGS prior and after renal transplantation. Obinutuzumab may offers some advantages. In the unique study performed in patients with multidrug dependent nephrotic syndrome reporting positive effects, obinutuzumab was associated with the anti-CD38 monoclonal antibody daratumumab proposing the unexplored frontier of combined therapies. Obinutuzumab represent an evolution also in the treatment of autoimmune glomerulonephritis, such as membranous nephrotahy and lupus nephritis. Results of randomized trials, now in progress, are awaited to add new possibilities in those cases that are resistant to other drugs. The aim of the present review is to open a discussion among nephrologists, with the hope to achieve shared approaches in terms of type of antibodies and doses in the different proteinuric renal conditions.